Psychological Antecedents to Intention to Quit (Journal of Organizational Psychology, 2023)
A random sample of adults was surveyed to explore the relationships among derailment, productivity propensity, and intention to quit. Derailed individuals perceive a lack of self-continuity and productivity propensity represents individuals’ disposition to perform tasks in a timely manner. Results indicated that intention to quit was positively affected by derailment and negatively affected by productivity propensity. Managerial implications of the findings, as well as directions for future research was discussed.
Keywords: organizational psychology; derailment; productivity propensity; intention to quit